BCAT2-mediated BCAA catabolism is critical for development of pancreatic ductal adenocarcinoma - Li, Jin-Tao; Yin, Miao; Wang, Di; Wang, Jian; Lei, Ming-Zhu; Zhang, Ye; Liu, Ying; Zhang, Lei; Zou, Shao-Wu; Hu, Li-Peng; Zhang, Zhi-Gang; Wang, Yi-Ping; et al. (Nature cell biology, 2020)
Branched-chain amino acid (BCAA) metabolism is potentially linked with development of pancreatic ductal adenocarcinoma (PDAC) 1 - 4 . BCAA transaminase 2 (BCAT2) was essential for the collateral lethality conferred by deletion of malic enzymes in PDAC and the BCAA–BCAT metabolic pathway contributed to non-small-cell lung carcinomas (NSCLCs) other than PDAC 3 , 4 . However, the underlying mechanism remains undefined. Here we reveal that BCAT2 is elevated in mouse models and in human PDAC. Furthermore, pancreatic tissue-specific knockout of Bcat2 impedes progression of pancreatic intraepithelial neoplasia (PanIN) in LSL-Kras G12D/+ ; Pdx1-Cre (KC) mice. Functionally, BCAT2 enhances BCAA uptake to sustain BCAA catabolism and mitochondrial respiration. Notably, BCAA enhances growth of pancreatic ductal organoids from KC mice in a dose-dependent manner, whereas addition of branched-chain α-keto acid (BCKA) and nucleobases rescues growth of KC organoids that is suppressed by BCAT2 inhibitor. Moreover, KRAS stabilizes BCAT2, which is mediated by spleen tyrosine kinase (SYK) and E3 ligase tripartite-motif-containing protein 21 (TRIM21). In addition, BCAT2 inhibitor ameliorates PanIN formation in KC mice. Of note, a lower-BCAA diet also impedes PDAC development in mouse models of PDAC. Thus, BCAT2-mediated BCAA catabolism is critical for development of PDAC harbouring KRAS mutations. Targeting BCAT2 or lowering dietary BCAA may have translational significance. Li et al. show that BCAA transaminase 2 enhances uptake and catabolism of branched-chain amino acids, thereby promoting development of pancreatic ductal adenocarcinoma harbouring KRAS mutations.